2015
DOI: 10.4103/1319-2442.168668
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis and intracranial bleed in a child with steroid-resistant nephrotic syndrome

Abstract: Meningitis and associated intracranial bleeding have been rarely reported in patients with steroid-resistant nephrotic syndrome. We present such a case with raised intracranial tension in a 13-year-old child and discuss the management issues. Prompt recognition and appropriate treatment of these complications can be life saving in a child with nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the present study, in a population of 10 461 NS patients, only 15 (0.14%) patients were identified as NS with cerebral hemorrhage, reflecting a low incidence rate. It has previously been reported that cerebral hemorrhage can occur in NS patients without conventional stroke risk factors [3,4]. Similarly, in the present study, 7 NS patients who had no conventional vascular risk factor records developed cerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In the present study, in a population of 10 461 NS patients, only 15 (0.14%) patients were identified as NS with cerebral hemorrhage, reflecting a low incidence rate. It has previously been reported that cerebral hemorrhage can occur in NS patients without conventional stroke risk factors [3,4]. Similarly, in the present study, 7 NS patients who had no conventional vascular risk factor records developed cerebral hemorrhage.…”
Section: Discussionsupporting
confidence: 80%
“…Cerebral hemorrhage lesions are mainly located in the lobes and subcortical regions [19]. In previous studies, hemorrhage lesions were located at the occipital lobe in many cerebral hemorrhage patients who had NS [3,4,6,20]. Some researchers have speculated that the occipital lobe hemorrhage may have resulted from small blood vessel damage caused by the deposition of immune substances [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations